A Brief History of Western Civilization : The Unfinished Legacy : Volume II : Since 1555 - Kishlansky, Mark ; Geary, Patrick and O'Brien, Patricia (New York Pearson/Longman, 2005)
Focusing on the Western civilization, this book provides coverage of an array of historical figures and events. It covers social as well as economic, religious, and cultural history within a traditional, and political framework. It explores everyday events and ordinary people as well as momentous affairs and elites
Include Color Illustration and Index
Keywords: Civilization, Western